Molecular responses at 3 and 6 months after switching to a second-generation tyrosine kinase inhibitor are complementary and predictive of long-term outcomes in patients with chronic myeloid leukemia who fail imatinib. Issue 6 (June 2015) - Boquimpani, Carla; Schaffel, Rony; Biasoli, Irene; Bendit, Israel; Spector, Nelson
Abstract Early molecular response (MR) defined by BCR–ABLIS levels has prognostic impact in chronic myeloid leukemia (CML). MR was evaluated at 3 and 6 months after switching to nilotinib or dasatinib in 115 patients with resistance to imatinib. Three groups were delineated at 3 months (< 1%, 1–10% or > 10% BCR–ABLIS levels) with different outcomes at 3 years regarding major molecular response (MMR, 91%, 47%, 22%, p < 0.001), failure-free survival (FFS), progression-free survival (PFS, 96%, 89% and 78%, p = 0.05) and overall survival (OS). After 6 months, patients with MR < 1% had higher 3-year MMR (83% vs. 16%, p < 0.001), FFS, PFS (94% vs. 84%, p = 0.05) and OS. Four patients had 3-month and 6-month MR > 10% and < 1%, respectively (3-year FFS 50%). Thirteen had 3-month and 6-month MR < 10% and ≥ 1%, respectively (3-year FFS 38%). These findings confirm the strong predictive value of 3-month and 6-month BCR–ABLIS levels in imatinib-resistant patients.